Desain Diameter Pipa secara Matematis pada Pembangkit Listrik Panas Laut (Oceans Thermal Energy Conversion) - Andi Hendrawan; Lusiani Lusiani; Aji Kusumastuti Hendrawan (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The issue of renewable energy is something that has often been discussed, especially since oil reserves are running low, the electricity supply that is indispensable for the sustainable development of infrastructure. One of the renewable energy sources is the marine thermal energy conversion system (OTEC). Renewable energy in time will become the mainstay of national and world energy because in fifty years an energy crisis may occur. OTEC's energy sources are re-emerging because of fears that an energy crisis will occur. The purpose of this study was to determine the mathematical model of the Popa OTEC design. The OTEC design is inseparable from the plumbing device, both cold water pipes, warm water and NH3 water. This research is a mathematical model of pipe design in a marine thermal power plant. The research begins with a literature review, namely previous research on OTEC (oceans thermal energy coversion). The results of the research are the determination of the diameter formula used to determine the pipe diameter, for cold seawater, warm seawater and NH3 or ammonia pipes. The design can be used to determine the variable diameter of the pipe with variations in discharge and flow velocity.